The Implementation of Islamic Religious Education Values in Building Anti-Usury Awareness among Senior High School Students - Said Ba'asyir Ar'rafi; Isti Fajri Khairunnisa; Novita Eka Paradina (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
The increasing use of interest-based financial products (riba) among students has become a growing concern, particularly with the proliferation of online lending platforms, buy-now-pay-later (BNPL) schemes, and consumerist lifestyles promoted through social media. This study aims to analyze the implementation of Islamic Religious Education (IRE) values in fostering anti-riba awareness among students and to identify the supporting and inhibiting factors influencing its effectiveness. The research employed a sequential explanatory mixed-methods design, beginning with a quantitative phase followed by a qualitative phase to gain deeper insights into the findings. The quantitative sample consisted of 240 senior high school and Islamic senior high school students in Jambi, selected through stratified random sampling. Data were collected using a standardized questionnaire (Cronbach’s α = 0.87) and semi-structured interview guides administered to six Islamic Religious Education teachers and twelve students. Quantitative and qualitative data were analyzed using SPSS version 26 and NVivo 14, respectively. The results revealed a significant positive correlation between the implementation of Islamic Religious Education values and students’ anti-riba awareness (r = 0.684, p < 0.01). Thematic analysis identified three main strategies: (1) cognitive-spiritual internalization through the integration of Qur’anic verses, Hadith, and contemporary Islamic legal opinions (fatwas); (2) affective role modeling and the establishment of a consistent school culture; and (3) contextual practices based on Islamic financial literacy and project-based learning activities. These findings demonstrate that a holistic and integrated Islamic Religious Education approach is effective in fostering anti-riba awareness among students. However, its success requires strengthening teachers’ capacities, enhancing multi-stakeholder collaboration, and adapting curricula to the dynamics of the digital financial ecosystem. This study contributes to the development of value-based educational models that are responsive to contemporary economic challenges faced by younger generations.